Energy Consumption of Bitcoin Mining - Bondarev, Mikhail (International Journal of Energy Economics and Policy, 2020)
Blockchain is one of the most popular terms associated with changes in the technological paradigm-taking place within the framework of the so-called "fourth industrial revolution". The Proof of Work algorithm is used for process transactions and ensure security in the Bitcoin network. The paper aims energy consumption of bitcoin mining. It implies the need for a network participant to solve a certain cryptographic task with energy consumption and predetermined final time for its completion. The methodology includes the analysis of relationship between active, reactive and apparent power is determined by the phase angle between the current and voltage in the network, more precisely, with the cosine of this angle - cosÏ† (power factor news). A correctly solved task is accepted by the network and included in the public transaction register. The participant who first provided such a solution receives a block reward. The main finding is that the solution of the energy consumption problem by other network participants, an order of magnitude less time is required. Keywords: industrial mining farms, Bitcoin mining, power factor reactive power, reactive power compensators JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9276